THE DEVELOPMENT OF ANIMATION VIDEOS FOR TEACHING ENGLISH INTEGRATED SKILLS FOR YOUNG LEARNERS - Tri Pujiani; Neilia Almustaflikhah (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2022)
As a foreign language, English is very good to be taught from an early age because an early age is a golden age where children can understand learning material faster. However, teaching English to young learners is not easy. They are easily bored, and also easily distracted. Thus, teachers are required to provide fun and interesting learning activities. Therefore, researchers developed media in the form of animation videos to assist teachers in conveying learning to students as well as attracting their attention. This media does not only refer to vocabulary but also listening, reading, speaking, and writing. In this study, researchers used the ADDIE development model (analysis, design, development, implementation, evaluation). The data in this study were collected by observation, distributing questionnaires, and interview methods. The instruments used in collecting data are questionnaires and tests. After doing research, it is proven that by applying animation video media, the level of student learning is increasing. In conclusion, teachers are advised to apply animation videos in teaching English for young learners so that the teaching and learning process becomes effective and fun.